If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x)(2x + 8y) = 0 Remove parenthesis around (5x) 5x(2x + 8y) = 0 (2x * 5x + 8y * 5x) = 0 Reorder the terms: (40xy + 10x2) = 0 (40xy + 10x2) = 0 Solving 40xy + 10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '10x'. 10x(4y + x) = 0 Ignore the factor 10.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(4y + x)' equal to zero and attempt to solve: Simplifying 4y + x = 0 Reorder the terms: x + 4y = 0 Solving x + 4y = 0 Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 x + 0 = 0 + -4y x = 0 + -4y Remove the zero: x = -4y Simplifying x = -4ySolution
x = {0, -4y}
| 3x^2+82x+418=0 | | 6x(30+6)=6 | | .11y+.09(y+8000)=2520 | | 11y+.09(y+8000)=2520 | | (5x)(10xy)= | | 0.5x+2=5x-43 | | 12h=9+84 | | b^2+6b-4=-2 | | 27x=9x-2 | | h(x)=4x^2+36 | | (cosx*cosy-cotx)dx-(senx*seny)dy=0 | | x^2-22x+437=0 | | -46+3x=80+12x | | (cosx*cosy-cotx)dx-(sinx*siny)dy=0 | | 11y=165 | | 3x^2+4x+14=0 | | 0.8+4.8=7.2 | | z-9.2=8.5 | | 6r-1+6r=119 | | 0=1.2z-3.6 | | 11z=99 | | -6.5=1.3y-1.3 | | -6=w+19 | | a+96-16=214 | | -34+1.7x=-11.9 | | 3+7m-1=6m+8-2m | | ((y^2)-(2xy)+(6x))dx-((x^2)-(2xy)+(2))dy=0 | | 11-z=5 | | 11-z=15 | | ((y^2)-(2xy)+(6x))dx-((x^2)-(2xy)+(2))=0 | | J(x)=0.75x^2 | | 8=16+12 |